Análisis de Requerimientos para Sistemas Gestores de Inventarios en Empresas Comercializadoras de Alimentos Empaquetados en Boyacá (2022)
The management and registration of inventories is part of a neuralgic process of organizations, since they represent storage costs that must be treated in the most optimal way possible. For this reason, it is proposed to analyze the requirements for inventory management systems in packaged food marketing companies in Boyacá, this in order to increase the efficiency in the management and control of inventories by reducing costs. To know the management that these have, a characterization of inventory management was carried out through the application of a survey, which took into account the dependent and independent variables, related to the management and control of inventories, subsequently the Inventory policy and methodologies based on the bibliography found, which recommended the use of this type of method depending on the sector to which the companies belong. Also to strengthen the choice of the correct methodology, a matrix was designed that analyzed some aspects related to inventory management. Finally, it is concluded that during the investigation certain shortcomings could be visualized in terms of the qualification of the personnel that could generate a barrier that prevents the correct functioning of the inventory management system